DTC analysis of DCMLI driven PMSM-SVM drive - Shriwastava, Rakesh G.; Pokle, Pravin B.; Mendhe, Ajay M.; Dhote, Nitin; Rewatkar, Rajendra M.; Mapari, Rahul; Dhunde, Ranjit; Bhagat Patil, Hemant R.; Pawase, Ramesh (Institute of Advanced Engineering and Science, 2025)
The paper focuses on a comparative analysis of direct torque control (DTC) space vector modulation (SVM) based permanent magnet synchronous motor (PMSM) drive. This comparative analysis is based on a conventional inverter and a 3-level dual-cell modular multilevel inverter (DCMLI) using the SVM technique using MATLAB simulation. The present DTC-PMSM drive consists of flux and torque hysteresis comparators and has a problem of switching frequency and torque ripple. The problems are solved by using SVM to provide more inverter voltage and it compensates for torque and flux error in a DTC. A reference voltage space vector is calculated every time using the algorithm on the basic of torque error and stator flux angle. It was proposed to control torque, torque angle, and stator flux in DTC-PMSM. From the detailed comparison, the DTC-DCMLI PMSM drive has an exact solution of problem-solving of switching frequency and torque ripple due to less distorted output. Proposed drives can be applicable for hardware implementation in automotive applications.